Efektivitas Rehabilitasi Bagi Pengguna Narkotika Sebagai Hak Tersangka - Rekas Bagarlo Rivan; Eko Raharjo; Fristia Berdian Tamza; Mamanda Syahputra Ginting; Firganefi (Program Studi Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas Sumatera Selatan, 2026)
This study aims to analyze the effectiveness of rehabilitation for narcotics users as a legal right for suspects, focusing on how regulations, implementation, and social factors influence the success of rehabilitation programs. This research uses a qualitative descriptive approach based entirely on secondary data. Sources include laws and regulations such as Law No. 35 of 2009 on Narcotics, government regulations, joint regulations on integrated assessment, court decisions, reports from the National Narcotics Agency (BNN), Ministry of Health publications, and relevant academic literature. Data were analyzed through content analysis and descriptive methods to evaluate policy implementation, program effectiveness, and challenges in rehabilitation practices. The study found that while regulations recognize rehabilitation as a right for narcotics users, implementation is not fully effective. Challenges include limited rehabilitation facilities, lack of professional staff, inconsistent application of integrated assessments, weak coordination between law enforcement and health institutions, and social stigma. These factors result in many users receiving imprisonment instead of rehabilitation, reducing overall program effectiveness. Rehabilitation is normatively guaranteed but not fully realized in practice. Effective rehabilitation requires improvements in facility availability, integrated assessment implementation, post-rehabilitation support, public education to reduce stigma, and stronger coordination between law enforcement and health institutions. This study relies solely on secondary data, limiting direct observation of rehabilitation practices and first-hand insights from stakeholders or users. The study provides insights for policymakers, law enforcement, healthcare providers, and researchers on the implementation gaps and strategies to enhance rehabilitation effectiveness. It contributes to the fields of criminal law, public health, and social rehabilitation programs.Keywords: narcotics rehabilitation, suspect rights, program effectiveness, law implementation, public health